The river - Paulsen, Gary. (New York Delacorte Press, 1991)
Because of his success surviving alone in the wilderness for fifty-four days, fifteen-year-old Brian, profoundly changed by his time in the wild, is asked to undergo a similar experience to help scientists learn more about the psychology of survival.
Sequel to Hatchet.
Keywords: Survival -- Fiction; Self-reliance -- Fiction